A positively charged aggregation-induced emission (AIE) luminogen as an ultra-sensitive mechanochromic luminescent material: design, synthesis and versatile applications. (23rd February 2021) - Yin, Weidong; Yang, Zengming; Zhang, Shaoxiong; Yang, Yuan; Zhao, Lixia; Li, Zhao; Zhang, Bo; Zhang, Shengjun; Han, Bingyang; Ma, Hengchang
Abstract : Nowadays, the rational design of a mechanochromic luminescent (ML) material with ultra-sensitivity toward external stimuli is a greatly challenging task. Abstract : Nowadays, the rational design of a mechanochromic luminescent (ML) material with ultra-sensitivity toward external stimuli is a greatly challenging task. In this contribution, TPA–Pyr–BP is readily synthesized and verified as a typical AIE luminogen (AIEgen), which consists of a twisted electron donor of triphenylamine (TPA) and a strong electron acceptor of pyridinium (Pyr), and this structural fabrication method shows an elevated electron D–A interaction and intra-molecular charge transfer (ICT) behavior. Specifically, due to the presence of a benzophenone (BP) derivative within the molecular structure, TPA–Pyr–BP exhibits a strong UV absorption ability ( ε = 42 360 L mol −1 cm −1 ). In contrast to a variety of analogues, TPA–Pyr–BP shows ultra-sensitivity with regard to the stimuli of mechanical force, and a sharp signal contrast is expressed with not only a large fluorescence intensity enhancement, but also an obvious emission wavelength shift of 102 nm. Then, the corresponding sensitive performance is extended to demonstrations of different applications, such as being used as a mechanosensor, solid material surface damage reporter, and fingerprint information extractor, as well as in the preparation of security papers. It is also found that the different aggregation states of TPA–Pyr–BP are responsible for this smart behavior.